PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI PADA UD. TRUBUS BARU - Gunawan Aji; Aulia Rahma Diniya Putri; Windi Cindiana; M. Mirza Muhaimin (PT. Hafasy Dwi Nawasena, 2023)
Responsibility accounting, companies can cut wasteful spending and ensure organizational resources are used effectively to achieve company goals. The purpose of this research is to find out whether the implementation of responsibility accounting which is used as a cost control tool in companies is effective and efficient at UD Company. New Trubus. The analytical method used in this research is the library research method with primary data obtained directly from UD. New Trubus. The research results show that the company UD. Trubus Baru has been quite effective in implementing responsibility accounting as a cost control tool. This can be seen from the budget prepared by UD. New Trubus. Where there are annual differences in raw material costs, direct labor and factory overhead costs. This shows the company's ability to allocate raw material costs, labor and factory overhead costs.